First-line antibiotic susceptibility pattern of toxigenic Corynebacterium diphtheriae in Indonesia - Husada, Dominicus (BMC Infect Dis, 2019)
BACKGROUND: Diphtheria has been reported as an outbreak in some regions in Indonesia, most especially in East Java Province. Resistance to penicillin, erythromycin, and other antibiotics, single or multiple, has been reported in several studies. This study aims to evaluate the first-line antibiotic susceptibility pattern of toxigenic Corynebacterium diphtheriae isolates. METHODS: This descriptive observational study was performed from August to November 2018. C. diphtheriae isolates were collected from diphtheria patients and carriers in East Java from 2012 to 2017 and kept at the Balai Besar Laboratorium Kesehatan Daerah Surabaya or the Public Health Laboratory of Surabaya. Sample selection was done by random cluster sampling. The sensitivity test by E-test®of the five antibiotics (penicillin, oxacillin, erythromycin, azithromycin, and clarithromycin) was done to determine the minimum inhibitory concentration (MIC). The Clinical and Laboratory Standards Institute M45A (2015) Corynebacterium spp. for penicillin and erythromycin was used as standard. RESULTS: From 114 targeted isolates, 108 were viable and toxigenic. The E-test was performed on the viable isolates. The majority of the hosts were male (58.3%), with median (range) age of 6.5 (1–14) years. Half of the samples were from the 1 to 5-year-old age group. The isolates were acquired much more from patients (78.7%) than carriers (21.3%) and from pharyngeal swab (74.1%). Most of these isolates were from Madura Island (47.2%) and the northern and eastern parts of the province (horseshoe area). Mitis isolates were the major variant (76.9%). The susceptibility pattern of C. diphtheriae to erythromycin was better than that to penicillin. The E-test result for penicillin was 68.52% susceptible, 31.48% intermediate, and 0% resistant (MIC range, < 0.016 to 2 μg/L) and for erythromycin (MIC range, < 0.016 to > 256 μg/L) was 85.2% susceptible, 12% intermediate, and 2.8% resistant The MIC range for oxacillin was 1 to 96 μg/L, while for both azithromycin and clarithromycin were <  0.016 to > 256 μg/L. CONCLUSION: The susceptibility rate of C. diphtheriae to erythromycin is higher than that to penicillin. The regular update of antibiotic selection to the national guidelines is recommended. The MIC reference standard to azithromycin and clarithromycin is also needed.